2005
DOI: 10.1093/humrep/deh888
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to bisphenol A is associated with recurrent miscarriage

Abstract: Exposure to bisphenol A is associated with recurrent miscarriage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
197
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(215 citation statements)
references
References 26 publications
4
197
1
3
Order By: Relevance
“…The role of endocrine disruptors as the main source of exposure to exogenous estrogens has been focused in present study on the basis of tissue levels of Aryl hydrocarbon Receptor (AhR). AhR mediates the effects of many xenoestrogens and endocrine disruptors and contributes to the loss of normal ovarian function in polluted environments (Sugiura-Ogasawara, 2005;Valdez, 2009). We have detected its roles on the incidence of LMA in this case control study which was conducted in the most polluted and populated city of Iran, Tehran comparing with Mashhad as the second most populated city (not polluted) of Iran.We considered the existence of refinery center with 220,000 bbl/d installed capacity and extensive diesel exhaust in Tehran as the major source of difference between these two mentioned cities.Other than citizenship factors we looked for exposure to many other resources of exposure to endocrine disruptors by recording their food habits and lifestyle factors which may induce the AhR levels in target tissues (Zelieann, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…The role of endocrine disruptors as the main source of exposure to exogenous estrogens has been focused in present study on the basis of tissue levels of Aryl hydrocarbon Receptor (AhR). AhR mediates the effects of many xenoestrogens and endocrine disruptors and contributes to the loss of normal ovarian function in polluted environments (Sugiura-Ogasawara, 2005;Valdez, 2009). We have detected its roles on the incidence of LMA in this case control study which was conducted in the most polluted and populated city of Iran, Tehran comparing with Mashhad as the second most populated city (not polluted) of Iran.We considered the existence of refinery center with 220,000 bbl/d installed capacity and extensive diesel exhaust in Tehran as the major source of difference between these two mentioned cities.Other than citizenship factors we looked for exposure to many other resources of exposure to endocrine disruptors by recording their food habits and lifestyle factors which may induce the AhR levels in target tissues (Zelieann, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Seventeen studies have measured BPA in blood and serum samples from healthy male and nonpregnant female adults (Dirtu et al 2008;Fung et al 2000;He et al 2009;Hiroi et al 2004;Ikezuki et al 2002;Inoue et al 2000Inoue et al , 2001Kaddar et al 2009;Kuroda et al 2003;Liu et al 2007;Sajiki et al 1999;Sugiura-Ogasawara et al 2005;Takeuchi and Tsutsumi 2002;Takeuchi et al 2004;Volkel et al 2005;Yang M et al 2009;Yoshimura et al 2002) (Table 3). Of these studies, five used ELISA, one used a radioimmunoassay (RIA), and the remainder used analytical chemistry to assess BPA concentrations.…”
Section: Internal Dosage Assessment From Blood Measures Of Bpamentioning
confidence: 99%
“…For instance, BPA levels in blood have been associated with a variety of conditions in women, including obesity, endometrial hyperplasia, endometriosis, recurrent miscarriages, sterility, and PCOS (reviewed by Vandenberg et al 2007). Other studies detected associations between high BPA exposure and chromosomal abnormalities, including pregnancies with fetuses that had an abnormal karyotype (Yamada et al 2002), recurrent miscarriage (Sugiura-Ogasawara et al 2005), and sister chromatid exchange measured in peripheral lymphocytes (Yang et al 2006). These epidemiological studies have several limitations, including small sample sizes, insufficient information on subject selection criteria, and crosssectional designs that failed to adequately control for potential confounders (Vandenberg et al 2007), thus preventing accurate assessments regarding the potential health risks of BPA.…”
Section: Relationships Between Measured Bpa Concentrations and Diseasmentioning
confidence: 99%
“…Studies on xenoestrogens, such as methoxychlor (MXC) and bisphenoyl A (BPA), have shown that exposure to these chemicals also alters the Hoxa10 expression in female reproductive tract (Block et al 2000;Suzuki et al 2004;Fei et al 2005;Markey et al 2005;Sugiura-Ogasawara et al 2005;Daftary and Taylor 2006;Smith and Taylor 2007). MXC is a pesticide and this chemical is associated with female reproductive defects after either prenatal or postnatal exposure.…”
Section: Estrogens and Progesterone Regulate Hox Gene Expression In Tmentioning
confidence: 99%